The Rise of Trump : America's Authoritarian Spring - MacWilliams, Matthew C.; Project Muse. (Amherst, Massachusetts : Amherst College Press, 2016)
The ascendance of Donald Trump to the presidential candidacy of the Republican Party has been both remarkable and, to most commentators, unlikely. The author argues that Trump's rapid rise through a bewildered Republican Party hierarchy is no anomaly; rather, it is the most recent expression of a long-standing theme in American political life, the tendency and temptation to an ascriptive politics--a political view that builds its basic case on ascribing to any relatively disempowered group (whether defined by race, ethnicity, gender, sexual orientation, religious belief, or other identifying category) a certain set of qualities that justify discriminatory treatment.--Publisher's description.
Description based on print version record.
Keywords: Trump, Donald, -- 1946-; Trump, Donald, -- 1946- -- Influence; Presidents -- Election; Political culture; Influence (Literary, artistic, etc.); Authoritarianism; Political culture -- United States; Authoritarianism -- United States; Presidents -- United States -- Election -- 2016.; United States; Electronic books